Business Model Innovation towards Competitive Advantage: Case Study in Indonesian Cosmetics and Herbal Health Companies - Anggraeni Permatasari; Wawan Dhewanto (Information Management and Business Review, 2013)
The dynamic changes in business environment make competition among company more tightly in the global market. This situation makes each company prepared innovation strategies to win global market competition. This research examined innovation strategies in two biggest cosmetic and herbal health companies in Indonesia. The author used case study with exploratory approach to find out how company developing innovation strategies and what factors that influence company in formulating those strategies. The author used canvas business modelling for analysis data. Data collection used secondary data which gained through the company profile and literatures review. This result indicates that innovation in value proposition, customer segments and key partners has become solution in helping cosmetic and herbal health industry strives to survive and be ready to face global business challenges.